Інноваційні вектори державної політики у сфері відновлення якості освіти в умовах тривалої кризи - Татарчук, Андрій Васильович; Равлюк, Тетяна Анатоліївна (My University, 2026)
This article analyzes the transformation of state governance mechanisms in ensuring the quality of general secondary education under martial law and the strategic planning of Ukraine’s post-war recovery. It is argued that the prolonged crisis, caused by full-scale aggression, has prompted a shift from traditional administrative oversight methods to flexible, service-oriented management models based on digitalization and adaptability. The dynamics of changes in state policy are presented through the prism of three key innovative vectors. The first–diagnostic-analytical–is based on the implementation and functioning of the information-analytical system “EvaluEd.” It is demonstrated that the transition to digital monitoring has transformed educational auditing from an external control instrument into an effective mechanism for strategic self-analysis of educational institutions and objective assessment of educational losses at the community level. The second vector–safety-oriented–is considered a fundamental prerequisite for the resumption of in-person learning. Based on the systematization of priority challenges, the study highlights issues such as insufficient shelter capacity, limited inclusive access to protective facilities, and the shift from situational to objective funding of capital construction based on educational environment indicators. The third vector–adaptive-digital–is revealed through an analysis of the evolution of the “All-Ukrainian Online School” platform. It is determined that the platform has transformed from a repository of learning content into an integrated institutional core of the digital education ecosystem. Special attention is paid to functional modules for diagnosing learning gaps and providing methodological support for teachers, enabling the scaling of personalized learning trajectories across the entire country. In conclusion, it is emphasized that the synergy of these vectors establishes a new paradigm of educational management, where digitalization serves as a cross-cutting tool for ensuring quality.
Keywords: state policy, quality of education, diagnostic-monitoring direction, safety vector, adaptive-digital ecosystem